2018
DOI: 10.3390/rs10091356
|View full text |Cite
|
Sign up to set email alerts
|

Airborne and Terrestrial Laser Scanning Data for the Assessment of Standing and Lying Deadwood: Current Situation and New Perspectives

Abstract: LiDAR technology is finding uses in the forest sector, not only for surveys in producing forests but also as a tool to gain a deeper understanding of the importance of the three-dimensional component of forest environments. Developments of platforms and sensors in the last decades have highlighted the capacity of this technology to catch relevant details, even at finer scales. This drives its usage towards more ecological topics and applications for forest management. In recent years, nature protection policie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
39
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(43 citation statements)
references
References 120 publications
3
39
0
1
Order By: Relevance
“…For the lidar-only scenario we found an increase in total CDW in the intact forests with increasing values of the 75th percentile of last returns, a metric related to the overall increase in both canopy and understory height and a correlate of total biomass. Our results are consistent with Chao et al (2009), who also found a weak correlation between total CDW and live biomass, whereas Martins et al (2015) related CDW stocks to mean biomass per tree. Logging and fire differentially affected CDW in Amazonian degraded forests.…”
Section: Land Use Equationsupporting
confidence: 92%
See 1 more Smart Citation
“…For the lidar-only scenario we found an increase in total CDW in the intact forests with increasing values of the 75th percentile of last returns, a metric related to the overall increase in both canopy and understory height and a correlate of total biomass. Our results are consistent with Chao et al (2009), who also found a weak correlation between total CDW and live biomass, whereas Martins et al (2015) related CDW stocks to mean biomass per tree. Logging and fire differentially affected CDW in Amazonian degraded forests.…”
Section: Land Use Equationsupporting
confidence: 92%
“…Hayek et al (2018) found 61.0 ± 14.8 Mg ha −1 of CDW stock in the Tapajós National Forest (51.3 ± 18.8 Mg ha −1 from this study). Martins et al (2015) reported a range of 6.7-72.9 Mg ha −1 of CDW stock in the Reserva Adolpho Ducke (mean of 41.6 and range of 22-60 Mg ha −1 from this study). Keller et al (2004) found an average of 55.2 ± 4.7 and 74.7 ± 0.6 Mg ha −1 of fallen CDW in an intact and logged site, respectively, at Fazenda Cauaxi (54.2±8.8 and 84.6±27.5 Mg ha −1 from this study).…”
Section: Land Use Equationsupporting
confidence: 46%
“…LidR is a module also dedicated to lidar forestry applications [61,62]. Latest version to the time of writing (2.1) provides methods for reading LAS and LAZ formats, for ground classification, tree segmentation and extraction of descriptive metrics for further analyses.…”
Section: R-cran Modulesmentioning
confidence: 99%
“…It means that a tree will mask out e.g. other trees or buildings, and this effect is more enhanced when the branches and leaves are dense and complex (Marchi et al, 2018). This can be avoided by several TLS scanning position sites from different perspectives (Yang et al, 2016).…”
Section: Introductionmentioning
confidence: 99%